“Electron-10” higt voltage accselerator for double-sided irradiation of flexible materials - Valtman, D.S.; Ivanov, A.S.; Nikiforov, E.K.; Ovchinnickov, V.P.; Svinin, M.P.; Tolstun, N.G. (Вопросы атомной науки и техники, 1999)
The main goals we pursued during the accelerator design and development were to develop a compact self-shielded device for flexible materials irradiation in one pass which might be installed by a Customer into common industrial premises not equipped with any lifting devices. These goals were successfully achieved in the “Electron-10” accelerator design.